Criminal Act of Attack on Honor Following the Constitutional Court Decision No. 105/PUU-XXII/2024: Human Rights Perspective - Putri, Fadiza Amalia; Prawira, M. Rizki Yudha (Jurnal Daulat Hukum, 2025)
The criminal act of attack on honor under Article 27A of Law No.  1 of 2024, following Constitutional Court Decision Number 105/PUU-XXII/2024, reflects Indonesia’s ongoing effort to balance the protection of individual dignity with the constitutional guarantee of freedom of expression. This study aims to analyze the human rights implications of the Constitutional Court’s ruling, which clarifies the interpretation of the phrases “other person” and “a matter” in Article 27A. Employing a normative legal research method and a qualitative descriptive approach, the study examines statutory provisions and the Court’s reasoning through the principles of legality, necessity, and proportionality as articulated in international human rights standards. The findings indicate that the Court’s conditional interpretation—restricting “other person” to natural persons and defining “a matter” as “an act that demeans the honor or reputation of an individual”—constitutes a significant normative improvement toward legal certainty. However, law enforcement practice continues to reveal the potential for this article to be misused to silence criticism of public officials, generating a persistent tension between normative ideals and implementation realities. This research’s novelty lies in providing the first human rights–based analysis of Article 27A following the Constitutional Court’s ruling, offering a new framework for evaluating the proportionality of criminal restrictions on freedom of expression in Indonesia’s digital democratic era.